Oat avenanthramides induce heme oxygenase‐1 expression via Nrf2‐mediated signaling in HK‐2 cells. Issue 12 (11th September 2015) - Fu, Junsheng; Zhu, Yingdong; Yerke, Aaron; Wise, Mitchell L.; Johnson, Jodee; Chu, YiFang; Sang, Shengmin
Abstract : Scope: Numerous studies have shown that avenanthramides (AVAs), unique compounds found in oats, are strong antioxidants, though the mechanism of action remains unclear. Here, we investigated whether AVAs affect heme oxygenase‐1 (HO‐1) expression through the activation of Nrf2 translocation. Methods and results: We investigated the effects AVA 2c, 2f, and 2p on HK‐2 cells, and found that AVAs could significantly increase HO‐1 expression in both a dose‐ and time‐dependent manner. Furthermore, we found that AVA‐induced HO‐1 expression is mediated by Nrf2 translocation. The addition of N‐acetylcysteine (NAC), but not specific inhibitors of p38 (SB202190), PI3K (LY294002), and MEK1 (PD098059) attenuated AVA‐induced HO‐1 expression, demonstrating an important role for reactive oxygen species, but not PI3K or MAPK activation, in activating the HO‐1 pathway. Moreover, hydrogenation of the double bond of the functional α, β ‐unsaturated carbonyl group of AVAs eliminated their effects on HO‐1 expression, suggesting that this group is crucial for the antioxidant activity of AVAs. Conclusion: Our results suggest a novel mechanism whereby AVAs exert an antioxidant function on human health. Further investigation of these markers in human is warranted to explore the beneficial health effects of whole grain oat intake.